THE EFFECTIVENESS TEST OF MATOA (PometiaPinnata) ENDOPHYTIC BACTERIA TOWARDS BACTERIA NOSOCOMIAL INFECTION - Denny Chandra Halid (Journal of Health, Technology and Science (JHTS), 2020)
This study aims to determine the effectiveness of Matoa (Pometiapin-nata) endophytic bacteria towards bacteria nosocomial infection namely Pseudomonas aeruginosa and Staphylococcus epidermidis. The subjects in the study were Matoa plant endophytic bacterial isolates on the stem (tw-igs). The positive control used is meropenem & negative control of aquades. This type of research uses quasi-experiments with a research design us-ing the One-Group Time-Series Design. The result of the study shows that there are 2 endophytic bacterial iso-lates in Matoa plants namely BEM 1 and BEM 2. Both endophytic bacterial isolates can kill and inhibits bacterial nosocomial infections Pseudomonas aeruginosa and Staphylococcus epider-midis with inhibition zones in the range of 16mm-22mm with a strong category very strong that it has the po-tential to be used as an antibacterial